IMPORTANCE OF INFECTION CONTROL THROUGH SCREENING, INSPECTION, PROBLEM ANALYSIS AND TREATMENT PROCEDURES IN DENTAL PRACTICE - Sholekhah, Nur Khamilatusy; Suryawati, Chriswardani; Setyawan, Henry; Rahfiludin, M. Zen (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Oral and dental health service facilities are very at risk of infection. It found an increase in the frequency of microorganisms before 33.3% and after 80% of treatments in the air of the practice room and an increase in microorganisms before 18.3% and after 70% treatment on the surface of the dental unit.Method: This study aim to report integratively on infection prevention and control guidelines in dental and oral health facilities. The literature review used in this article uses the Systematic Literature Review method by analyzing 618 articles on the scientific search engines Science Direct, ProQuest, Google Schoolar and Pubmed with the criteria for articles related to keywords and 14 articles were collected as literature studies related to material. Result: Guidelines for the implementation of infection prevention in dental and oral health facilities.Conclusion: Effective and efficient infection control efforts in dentist practice can reduce the spread of infectious diseases in dental and oral health care facilities.